Potential of Dry-Cured Ham Bones as a Sustainable Source to Obtain Antioxidant and DPP-IV Inhibitory Extracts - Gisela Carrera-Alvarado; Fidel Toldrá; Leticia Mora (MDPI AG, 2023)
The utilization of animal bones as a protein source could be used as a sustainable pathway for the production of bioactive compounds. In this study, bones were pretreated with pepsin enzyme (PEP) and then sequentially hydrolyzed with Alcalase (PA) and Alcalase, as well as Protana prime (PAPP). The degree of hydrolysis, antioxidant activity, and DPP-IV inhibitory activity were measured. All three hydrolysates showed antioxidant and DPP-IV inhibitory activity; however, the highest result in both bioactivities was obtained with the PAPP hydrolysate. The obtained free amino acid content was 54.62, 88.12, and 668.46 mg/100 mL of hydrolyzed in PEP, PA, and PAPP, respectively. Pepsin pretreatment did not significantly affect the degree of hydrolysis; however, it is suggested that it promoted the cleavage of certain bonds for subsequent protease action. Accordingly, a total of 550 peptides were identified in PEP hydrolysate, 1087 in PA hydrolysate, and 1124 in PAPP hydrolysate using an LC-MS/MS approach. Pepsin pretreatment could be an effective method in the utilization of bone sources for the production of antioxidant and hypoglycemic peptides.